SURFACE MINES OF MINING AREA ŽACLÉŘ – CREATING AND USING OF FINANCIAL RESERVES FOR REMEDIATION AND RECLAMATION - Honová, Kristýna; Mališ, Jiří (GeoScience Engineering, 2018)
Abstract Companies engaged in mining are legally obliged to ensure remediation and reclamation of land affected by mining. Creation and use of financial reserves are subject to approval and control of the Mining Authorities. However, the methodology of creating financial reserves is decided by the mining company itself. In the paper, we describe the methods of creating financial reserves of a specific mining company GEMEC Union for remediation and reclamation after coal surface mining. The paper provides chronological comparisons of coal mining in two open pit mines, including the principles for creating and using financial reserves for remediation and reclamation. Keywords: Jan Šverma Mine (JŠM), remediation, reclamation, mining, financial reserves https://doi.org/10.2478/gse-2018-0007